2017
DOI: 10.1084/jem.20161900
|View full text |Cite|
|
Sign up to set email alerts
|

An essential role of high-molecular-weight kininogen in endotoxemia

Abstract: In this study, we show that mice lacking high-molecular-weight kininogen (HK) were resistant to lipopolysaccharide (LPS)-induced mortality and had significantly reduced circulating LPS levels. Replenishment of HK-deficient mice with human HK recovered the LPS levels and rendered the mice susceptible to LPS-induced mortality. Binding of HK to LPS occurred through the O-polysaccharide/core oligosaccharide, consistent with the ability to bind LPS from K. pneumoniae, P. aeruginosa, S. minnesota, and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Mice lacking HK ( Kng1 −/− ) were generated in our previous studies ( 22 ). Double knockout mice lacking both bradykinin receptors ( B1RB2R −/− ) were purchased from the Jackson Laboratory (Bar Harbor, ME, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Mice lacking HK ( Kng1 −/− ) were generated in our previous studies ( 22 ). Double knockout mice lacking both bradykinin receptors ( B1RB2R −/− ) were purchased from the Jackson Laboratory (Bar Harbor, ME, USA).…”
Section: Methodsmentioning
confidence: 99%
“…When human congenital FXI-deficient plasma was used, addition of Pep19-2.5 prevented HK degradation nearly complete over Binding of Pep19-2.5 to LPS prevents binding to HK. It has been recently shown that HK is an important LPS carrier and binding of LPS to HK triggers the inflammatory response 5 . Thus, blocking LPS binding to HK with Pep19-2.5 might be a promising strategy to prevent systemic inflammatory reactions.…”
Section: Pep19-25 Prevents Degradation Of Hk In Plasmamentioning
confidence: 99%
“…In an exciting paper, Yang and colleagues provide new insights into the role of the contact system in mouse models of endotoxemia . They show with compelling data, that HK is a major contributor to LPS‐induced lethality.…”
Section: Hk As Playmaker In Lethal Endotoxemiamentioning
confidence: 99%